2020
DOI: 10.1177/0095327x20973373
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Liabilities of Risk-Taking Propensity and Confidence at the U.S. Military Academy

Abstract: The military environment presents an intersection between a setting featuring unavoidable risk and individual risk-taking propensity; prior work suggests risk-takers have positive and negative outcomes here, and messaging about risk-taking in the military is mixed. The current study used social identity theory to examine how self-reported risk propensity related to three identities/outcomes among cadets at the U.S. Military Academy: attributes of an archetypal “Model Soldier” (physical and military excellence)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Their research did not deal with SLBs. A recent study focusing on the United States Military Academy (Schaefer et al, 2020) found that cadets with higher risk-taking propensity demonstrated superior military and physical performance, but had more behavioral problems, poorer grades, and showed a discrepancy between their confidence and conscientiousness-related attributes. We note that a single individual may exhibit different combinations of altruistic and intuitive behavior.…”
Section: Model and Hypothesesmentioning
confidence: 99%
“…Their research did not deal with SLBs. A recent study focusing on the United States Military Academy (Schaefer et al, 2020) found that cadets with higher risk-taking propensity demonstrated superior military and physical performance, but had more behavioral problems, poorer grades, and showed a discrepancy between their confidence and conscientiousness-related attributes. We note that a single individual may exhibit different combinations of altruistic and intuitive behavior.…”
Section: Model and Hypothesesmentioning
confidence: 99%
“…Furthermore, students' academic performance was positively related to their need for achievement, locus of control, and self-efficacy [108]. A positive relationship between academic performance and risk-taking propensity [109].…”
Section: Relationship Between Entrepreneurial Intention and Student A...mentioning
confidence: 99%